China as the Strategic Competitor in the Debate on TPP in the United States - Matera, Paulina (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
The Trans-Pacific Partnership (TPP) was negotiated with participation of the U.S. representatives from 2008. It was discussed not only in terms of the economic consequences of it. The proponents of signing TPP claimed that it would strengthen the alliances in Asia-Pacific region, curtail the Chinese influences and let the U.S. establish the global trade rules for the future. The debate on this issue took place in the Congress, also the front runners of the presidential elections of 2016 expressed their standpoints. The attitude of public opinion will be also presented as well as the position of Donald Trump which resulted in the withdrawal of the United States from the agreement once he became the President of the U.S.